Ate it anyway : stories - Allen, Edward, 1948- (Flannery O'Connor Award for Short Fiction., 2003)
In the limbo bounded by rebellion and resignation, belonging and solitude, Ed Allen's middle Americans seem to be either freely adrift or uncomfortably vested in an exit strategy wholly inadequate for their circumstances. These sixteen darkly humorous stories gauge the tension between what we really feel and what we outwardly express, what we should do and what we manage to get done. In ""Celibacy-by-the-Atlantic, "" Phil negotiates a lingering, low-intensity regret brought on by the annual family get-together at his parents' beach house, where memories of his aimless, privileged adolescence mi